TRAINING MANAGEMENT IN ISLAMIC BOARDING SCHOOL (Case Study on Sidogiri’s Islamic Boarding School Pasuruan) - Hindama Ruhyanani (KABILAH : Journal of Social Community, 2016)
Abstrak:Pesantren adalah pendidikan asli di Indonesia yang unik karena menampilkan karakter khas dan eksotis, memiliki keunggulan, baik dalam tradisi ilmiah yang dinilai sebagai salah satu tradisi serta transmisi dan internalisasi moral. Sementara di sisi lain, sekolah juga merupakan pendidikan yang dapat memainkan peran pemberdayaan dan transformasi sosial secara efektif. Pesantren mampu melakukan sumber daya manusia oleh manajemen pelatihan. Pertama, kebijakan pesantren dalam rangka mempertahankan eksistensi pondok pesantren adalah untuk meningkatkan kualitas dan kompetensi dari ulama. kemampuan ditingkatkan dalam bentuk kemampuan manajemen, kemampuan ekonomi dan kemampuan untuk menguasai materi. Kedua, manajemen pelatihan dari perencanaan evaluasi dilakukan seefektif mungkin dalam rangka meningkatkan kompetensi guru agama. Tapi konsep berkah selalu menemani pelaksanaan pelatihan. Kata Kunci: Manajemen Pelatihan, Pesantren Abstract:Boarding school is an original education (indegenious) in Indonesia, which is unique because it displays the typical character and the exotic, has the advantage, both in the scientific tradition which is rated as one of the great tradition (great tradition) as well as transmission and internalization of morality. While on the other hand, schools are also an education which can play the role of empowerment (empowerment) and social transformation (civil transformation) effectively. Pesantren able to perform human resource by training management. First, policy of boarding school in order to maintain the existence of the boarding school is to improve the quality and competence of the cleric as well as students. Enhanced capabilities in the form of management ability, the ability of the economy and the ability to master the material. Second, training management from planning to evaluation is carried out as effectively as possible in order to increase the competence of religious teacher and students. But the concept of blessing always accompany the implementation of the training. Keyword: Training Management, Islamic Boarding School